Synthesis of a MnO2–graphene foam hybrid with controlled MnO2 particle shape and its use as a supercapacitor electrode - Dong, Xiaochen (2013)
A simple approach was developed to synthesize the three-dimensional (3D) hybrid of manganese dioxide (MnO2) and graphene foam. The morphology of the MnO2 nanostructures can be readily controlled by the solution acidity. Furthermore, we demonstrate that, serving as a free-standing supercapacitor electrode, this novel three-dimensional hybrid gives a remarkable specific capacitance (560 F/g at the current density of 0.2 A/g) and excellent cycling stability.